Design of apolar chitosan-type adsorbent for removal of Cu(II) and Pb(II): An experimental and DFT viewpoint of the complexation process - Vieira, Camilla L.; Sanches Neto, Flávio O.; Carvalho-Silva, Valter H.; Signini, Roberta (Journal of environmental chemical engineering, 2019)
Chitosan-N-lauroyl (CL) was synthesized from the reaction between chitosan and lauroyl chloride, in two proportions, obtaining the adsorbents CL1P (1:1) and CL2P (2:1). These were used for studies in aqueous Cu(II) and Pb(II) solutions on the metal ion adsorption capacity and the metal/adsorbent interaction. The pH, temperature, kinetics, selectivity and adsorption equilibrium were investigated. The feasibility of complexation between the ions and the adsorbent was verified theoretically through a density functional theory (DFT) approach. The theoretical maximum adsorption capacities (qmax) of CL1P and CL2P for Cu(II)/Pb(II) ions were 36.4/41.0 and 48.5/37.6 mg g−1, respectively. The experimental qmax values were lower than the theoretical values and ranged from 31.5–33.0 mg g−1. At the optimum pH value (5.5) the ion adsorption process was spontaneous, endothermic and associated with pseudo-second-order kinetics. Supported by quantum mechanical calculations, the site of ion-chitosan interaction was identified, evidencing the role of carbonyl, hydroxyl and amide groups in the stabilization of the complexes. Considering the scarcity of studies on apolar chitosan-based adsorbents for the removal of heavy metals, the promising results presented herein allow a better understanding of the relation between apolar groups and pH control, which could aid the design of polymeric adsorbents.